Poly(methyl methacrylate-co-butyl acrylate)/organophosphate-modified montmorillonite composites - Sirapanichart, Sanit; Monvisade, Pathavuth; Siriphannon, Punnama; Nukeaw, Jiti (My University, 2011)
Poly(methyl methacrylate-co-butyl acrylate)/tetrabutylphosphonium modified montmorillonite (P(MMA-co-BA)/P-MMT) composite films were prepared by simple solution casting technique. P(MMA-co-BA) was synthesized through solution polymerization in the presence of benzoyl peroxide (BPO) as an initiator. After modification via cation exchange reaction by tetrabutylphosphonium bromide, the organoclay was dispersed in toluene and added into P(MMA-co-BA) solution. The well-dispersed mixture was cast by doctor blade technique to obtain the composite films. The P-MMT content in the composites was varied (i.e., 1, 2, 3 and 6 wt%) in order to study its effects on thermal stability, mechanical properties and UV shielding ability. The structure of P-MMT in the composites was investigated by XRD technique. The composites containing 1 and 2 wt% of P-MMT showed the d001 peak slightly shifted to lower 2θ, indicating mainly intercalated structure occurred with some agglomerations of particles. The intercalated structure of P(MMA-co-BA)/P-MMT 2% composites was observed by TEM technique. The TGA results showed that degradation of the composites occurred at higher temperatures compared to that of their virgin polymer and the degradation point increased with P-MMT content. Tensile strength and Young's modulus of composites were higher than those of their original copolymer. By addition of 1-3 wt% of P-MMT, it could be seen that the higher the P-MMT loading, the higher would be the tensile strength and Young's modulus. The P(MMA-co-BA)/P-MMT composite films showed their screening ability in UV region, especially in the UV-B range, which is rather higher than that in the visible region.
Keywords: Montmorillonite; Organoclay; Organophosphate; Poly(methyl methacrylate-co- butyl acrylate); Solvent casting